Effect of clopidogrel withdrawal on platelet reactivity and vascular inflammatory biomarkers 1 year after drug-eluting stent implantation: results of the prospective, single-centre CESSATION study. Issue 20 (27th July 2011) - Sambu, Nalyaka; Dent, Hazel; Englyst, Nicola; Warner, Timothy D; Leadbeater, Philip; Roderick, Paul; Gray, Huon; Simpson, Iain; Corbett, Simon; Calver, Alison; Morgan, John; Curzen, Nick
Abstract : Background: The optimal duration of clopidogrel treatment, particularly following drug-eluting stent (DES) implantation, remains contentious. Previous studies have observed a clustering of adverse events following clopidogrel cessation 1 year after DES, the aetiology of which is poorly understood. Objective: To investigate, in the prospective CESSATION study, the effect of clopidogrel withdrawal at 1 year after DES implantation on (i) arachidonic acid (AA)- and adenosine diphosphate (ADP)-induced platelet aggregation, and (ii) biomarkers of vascular inflammation, including soluble CD40 ligand (sCD40L), high-sensitivity C-reactive protein (hsCRP) and interleukin 6 (IL-6). Methods and results: The prospective CESSATION study was undertaken in 33 patients receiving aspirin and due to discontinue clopidogrel 1 year after DES. Platetet reactivity was measured using short thromboelastography, and compliance with aspirin determined from serum thromboxane B2 (TXB2 ) levels. Venesection was performed at 4 weeks and 24 h before, and at 24 h, 48 h, 1, 2 and 4 weeks after, clopidogrel cessation. Following clopidogrel withdrawal, there was (i) a predictable increase in ADP-induced platelet aggregation (ii) an unexpected significant increase in AA-induced platelet aggregation (iii) a decline in IL-6 and hsCRP at 1 week and 4 weeks respectively; and (iv) a non-significant increase in sCD40L at 4 weeks TXB2 levels were consistently suppressed, indicating complete inhibition of cyclo-oxygenase-1 by aspirin. Conclusion: An aspirin-independent, time-dependent increase in AA-induced platelet activation following clopidogrel withdrawal in patients with a DES has been described. New insights into a potential mechanism for the observed clustering of adverse events that occur early after clopidogrel cessation have been provided. These findings raise the question as to whether AA-induced clotting is an appropriate test of aspirin sensitivity.